Free fire eaudiobook - Box, C. J. (Joe Pickett, 2007)
Best-selling author C. J. Box-an Anthony and Macavity Award winner-earned starred reviews from both Publishers Weekly and Booklist for this exceptional mystery. Taking advantage of a legal loophole, a lawyer kills four people in Yellowstone National Park and walks away a free man. As the public outcry intensifies, the governor hires former game warden Joe Pickett to conduct a private investigation.